Pengaruh Kinerja Keuangan Terhadap Tingkat Pertumbuhan Berkelanjutan - Andari, Atik Tri; Aalin, Elmi Rakhma; Putranti, Eti (Gorontalo Accounting Journal, 2021)
This study aims to determine and analyze whether financial performance affects the level of sustainable growth. The selected companies are companies from trading and service companies in 2017-2019. Determination of the sample using purposive sampling method. This research uses multiple linear regression analysis with SPSS application. The results of this study indicate that the profitability ratio has no effect on the sustainable growth rate and the solvency ratio has a negative effect on the sustainable growth rate.